Validação de conteúdo de um instrumento para mensuração do esforço auditivo - Guijo, Laura Mochiatti [UNESP]; Horiuti, Mirella Boaglio; Cardoso, Ana Cláudia Vieira [UNESP] (FapUNIFESP (SciELO), 2020)
PURPOSE: To validate the content of an instrument to measure listening effort for hearing-impaired individuals. METHOD: This is a validation study, developed in two stages, which the Stage 1 is the planning and development of the first version of the instrument, and Stage 2 the investigation of the evidences of validity based on the content and development of the final version of the instrument to measure listening effort. Ten professionals with expertise in the field of audiology, with more than five years of clinical experience participated in this study. The instrument to be validated was composed of three parts: I - speech perception of logatomes and listening effort; II - listening effort and working memory and; III - speech perception of meaningless sentences and working memory and they were presented monoaurally, in quiet and in the signal-to-noise ratios + 5dB, 0dB and -5dB. It was conducted a descriptive analysis regarding the suggestions of the committee judge audiologists and the analysis of the individual and scale content validity index. RESULTS: The results showed that parts I and III which constitute the proposed instrument reached a scale content validity index above 0.78, which means that the presented items did not need modification in their construct. CONCLUSION: The evidences of validity studied allowed relevant modifications and made this instrument adequate to its construct.

OBJETIVO: Validar o conteúdo de um instrumento para mensuração do esforço auditivo para indivíduos com perda auditiva. MÉTODO: Trata-se de um estudo de validação, desenvolvido em duas fases, sendo a fase 1 o planejamento e desenvolvimento da primeira versão do instrumento e a fase 2 a investigação das evidências de validade baseadas no conteúdo do instrumento e desenvolvimento da versão final para mensuração de esforço auditivo. Participaram dez profissionais com expertise na área audiológica, com mais de cinco anos de experiência. O instrumento a ser validado foi composto por três partes: I - “percepção de fala de logatomas e esforço auditivo”; II - “esforço auditivo e memória operacional”; e III - “percepção de sentenças sem sentido e memória operacional”, apresentadas de forma monoaural no silêncio e nas relações sinal-ruído +5dB, 0dB e -5dB. Foi realizada a análise descritiva das sugestões do comitê de fonoaudiólogos e do índice de validade de conteúdo individual e total. RESULTADOS: Os resultados mostraram que as partes I e III do instrumento proposto atingiram o índice de validade de conteúdo total acima de 0,78, ou seja, os itens apresentados não necessitaram de modificações em seu constructo. CONCLUSÃO: As evidências de validade estudadas permitiram relevantes modificações e tornaram esse instrumento adequado ao seu constructo.
Content validation of an instrument to measure listening effort